Modeling of Buckling Restrained Braces Subjected to Dynamic loads - Hashem Shariatmadar; Hossein Abbaszadeh (مجله مدل سازی در مهندسی, 2009)
In this paper an effective, applicable method and a simple model are presented for accurate modeling of buckling restrained braces. In the beginning, all components of buckling restrained brace are defined. A test specimen of this brace type is completely modeled in ANSYS finite element program (complete model). The modeling is validated by comparing the nonlinear dynamic results with experimental results.A simple model consisted of core steel and spring is recommended, modeled, analyzed and evaluated. Based on the results a method is presented for calculating the spring stiffness. It elucidates that the spring prevents the buckling of steel core and fining the mesh elements size resulted in smaller spring constant. Comparison of the hysteresis curves indicates a good agreement between the experiment and models (simple and complete models). In general, the difference between the experimental and analytical results is less than five percent.